Robustness assessment approaches for steel framed structures under catastrophic events. (15th January 2015) - Formisano, A.; Landolfo, R.; Mazzolani, F.M.
Abstract: The current study deals with the robustness assessment methods of steel framed buildings under catastrophic events. Two steel framed buildings, designed according to old and new seismic Italian codes, have been herein analysed, by considering the uncertainties of both the material strength and the applied loads, through two investigation methods. First, within the methodologies used for robustness assessment under seismic loads, a deterministic method, framed within the Performance Based Seismic Design (PBSD), has been applied. Later on, the robustness of studied structures under different column-removed conditions, related to different catastrophic events (blast, impact, fire and so on), has been assessed by means of two force-based analysis techniques (a literature approach and a more advanced procedure) in order to estimate their resistance against progressive collapse. The application of the two methods has allowed to calculate the robustness index of examined structures, by taking into account the influence of both the catenary effect phenomenon and different beam-to-column joints, with the final aim to show their behavioural difference in terms of robustness.